2021
DOI: 10.34057/ppj.2020.39.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pelvic pain and pelvic organ prolapse: a consequence of upright position?

Abstract: Objective: The pathogenesis of chronic pelvic pain (CPP) is still incompletely understood. Generally accepted is, that soft tissue structures mutate with age, loose tension and by this can provoke CPP. This raises the question, of whether the bony pelvis underlies comparable age-dependent changes and if so, how this alteration has impact on the static anatomy of the pelvic floor and the suspension and supporting system. Materials and Methods: In order to answer this question we analysed the biological evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 16 publications
1
36
0
2
Order By: Relevance
“…Posterior fornix syndrome (PFS) symptoms may occur months or years after MUS, but may be present "below the surface" preoperatively, as shown by Goeschen 7 and others. [6][7][8] Late PFS symptoms are not necessarily the fault of the implant, or the surgeon. They are more likely a consequence of diverted pelvic forces onto USLs weakened from childbirth or aging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Posterior fornix syndrome (PFS) symptoms may occur months or years after MUS, but may be present "below the surface" preoperatively, as shown by Goeschen 7 and others. [6][7][8] Late PFS symptoms are not necessarily the fault of the implant, or the surgeon. They are more likely a consequence of diverted pelvic forces onto USLs weakened from childbirth or aging.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic algorithm, a foundation stone of the integral theory system, Figure 1, was used as a diagnostic guide for the surgical studies. [6][7][8] The algorithm, Figure 1, shows how the relationships between symptoms and loose ligaments, rectangle Figure 1, may cause pelvic dysfunctions. Finally showing how the hypothesis of USL causation of pain/bladder/ bowel dysfunctions, can be partly tested by speculum or pessary tests, and more fully by referral to published works which validate cure such symptoms following repair of USLs.…”
Section: In Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…7 1.4 | Cure of CPP cure by USL repair Since 1996, many surgical studies have reported cure of CPP and co-occurring bladder and bowel symptoms following USL repair, with or without slings. [8][9][10][11][12][13][14][15][16][17][18][19][20] F I G U R E 1 Diagnostic algorithm. Posterior fornix syndrome symptoms are contained in the posterior zone rectangle.…”
Section: Diagnosis Of Cpp Of Apparently Unknown Origin According To T...mentioning
confidence: 99%